Особенности структуры Простого пролога F 19-99 Библиотеки им. Врублевских АН Литвы: июнь–август - Сергеевна Самодурова, Юлия (Slavistica Vilnensis, 2010)
The article describes the structural features of the Old Church Slavonic Non-Metrical Synaxarion manuscript copy F 19-99 written within the first three decades of the 16th century and now kept in the Wróblewskie Library of the Lithuanian Academy of Sciences. The research which was limited to the three summer months (June–August), revealed that the hagiographical part of the manuscript contaminates two different versions of Non-Metrical Synaxarion with some entries of Metrical Synaxarion, while its edificatory part contains the texts typical of Non-Metrical Synaxarion in its expanded version and some additional entries tentatively related to the Second edition of the Old Church Slavonic Izmaragd. The article presents a list of new edificatory entries and their correspondences to the three main editions of Izmaragd.